Individual work performance questionnaire: Translation and validation in Chinese - Guihong Tang; Safiah Omar; Raida Abu Bakar (PLoS ONE, 2026)
The Individual Work Performance Questionnaire (IWPQ) serves as a recognized multidimensional instrument employed for the assessment of work performance, covering task performance, contextual performance, and counterproductive work behavior. Although extensively utilized, limited research has explored its psychometric attributes within the organizational framework in China. This study aims to bridge this research void by executing a comprehensive validation investigation with a sample of 833 Chinese workers. Multiple models including the three-factor model, higher-order model, and bi-order model demonstrating strong psychometric properties. Among these, the three-factor model was chosen for more detailed examination. The initial step involved conducting confirmatory factor analysis using AMOS, evaluating factors such as normality, factor loadings, reliability, common method bias, and overall model adequacy. Subsequently, a multigroup confirmatory factor analysis was performed to investigate measurement equivalence among subgroups based on gender. Following this, structural equation modeling in SmartPLS was utilized to assess criterion-related validity by examining the correlation between overall work performance and accomplishment as gauged by Seligman’s PERMA framework. The findings indicated robust psychometric characteristics, with factor loadings surpassing 0.70, high reliability and convergent validity (CR > 0.70 and AVE > 0.50), and adequate model suitability (RMSEA < 0.05). Assessment of measurement invariance validated the stability of the tripartite structure across genders, as evidenced by RMSEA values meeting criteria for both male and female cohorts. Criterion validity assessment unveiled a substantial positive correlation between overall individual work performance and accomplishment (β = 0.511, p < 0.001), denoting a noteworthy predictive capacity. These findings establish the IWPQ as a reliable and conceptually grounded instrument suitable for assessing individual work performance in Chinese organizational contexts.